2022
DOI: 10.1155/2022/4168308
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Assessment of Acupoint Therapy of Traditional Chinese Medicine on Cough Variant Asthma: A Meta‐analysis

Abstract: Acupoint application has been used in China to treat various illnesses for ages. In cough variant asthma (CVA), the main clinical sign is episodic night cough. Acupoint application therapy of traditional Chinese medicine is an effective procedure to treat cough variant asthma. The current study is designed to systematically assess the effectiveness of acupoint application therapy in traditional medicine for patients with cough variant asthma. The comprehensive computer retrieval related to comparison between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Acupuncture is an integral part of Traditional Chinese Medicine and can enhance the functioning of the patient’s immune system, thereby reducing phlegm and inflammation ( 31 ). According to a number of clinical reports, acupuncture and moxibustion have achieved good results in the treatment of cough, asthma, COPD and other lung diseases ( 19 - 21 ). For patients with poor drug treatment effect, you can try acupuncture treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture is an integral part of Traditional Chinese Medicine and can enhance the functioning of the patient’s immune system, thereby reducing phlegm and inflammation ( 31 ). According to a number of clinical reports, acupuncture and moxibustion have achieved good results in the treatment of cough, asthma, COPD and other lung diseases ( 19 - 21 ). For patients with poor drug treatment effect, you can try acupuncture treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that acupuncture can reduce the postoperative inflammatory response in patients undergoing lung surgery, thus reducing postoperative pulmonary complications such as cough ( 17 , 18 ). In addition, clinical studies have confirmed that acupuncture can achieve good results in the treatment of cough, asthma, chronic obstructive pulmonary disease (COPD) and other lung diseases ( 19 - 21 ). However, the mechanism of acupuncture in the treatment of chronic cough caused by pulmonary surgery is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%